Optimal power dispatch in wind farm based on reduced blade damage and generator losses. (April 2015) - Zhang, Jin-hua; Liu, Yong-qian; Tian, De; Yan, Jie
Abstract: For large wind farms, the unit combinatorial optimization research can improve the level of wind farm operation and increase the economic efficiency of wind farms. The blades, which not only account for 20% of the total wind turbine cost, but also have much influence on the wind turbine life, are important components of wind turbines. With the stress analysis of blade roots in four different load conditions, this paper establishes a mathematic model quantifying damage of the blades and its relationship with blade life. The relationship between generator losses and reactive power is also established according to the generator losses of wind turbines. Moreover, based on the theory of binary particle swarm algorithm, genetic algorithm and GA-IBPSO algorithm, three optimal power dispatch models are proposed. The models take wind power prediction and load demand of electrical system into consideration and the objective of the optimization are to minimize the blade damage and generator losses. Application of the proposed optimal dispatching model in a 49.5 MW wind farm has proved itself feasible and reliable in reducing the number of start-stop times, extending the unit life while meeting the load requirements.